Load-based generic polca: performance assessement using simulation - Fernandes, N.O.G. (2017)
Submitted by Nuno Fernandes (nogf@ipcb.pt) on 2017-07-25T13:52:31Z No. of bitstreams: 1 ICOMECYME 2017 Fernandes and Silva.doc: 2305024 bytes, checksum: 06eed4dd8e6f5b70e52b34536f5e71bd (MD5)